Effects of bilingualism on L3 vocabulary learning among Iranian EFL learners - Zare, Mostafa; Mobarakeh, Sajad Davoudi (Penerbit UKM, 2013)
It is well documented that everybody’s first language or mother tongue influences the way one learns his/her second language (Wade-Wolley, 1999; Liszka, 2004). However, the difference and comparison of this effect on third language learning motivated the researchers to investigate whether Arabic-Persian bilinguals(APBs) take advantage of their bilingualism in learning the third language (English) versus Persian monolinguals (PMs) or not. The study sample comprised of 100 male senior high school students who were randomly selected. 50 PM students were in one group and 50 APB students were in the other group. Firstly, a questionnaire through which mono/bilingualism and proficiency level in the language skills were asked was given to students. Then a list of English words was presented to the students and they were requested to write the meaning of words they knew. 50 words meaning of which none of the students in both groups knew were selected to be taught. For homogeneity purpose, Oxford Placement Test (OPT) was also used. After taking the pretest (based on 50 unknown words), students received the treatment (50 unknown words were taught). Finally, posttest was run and the performance of both groups onL3 general, recognition and production vocabulary was analyzed. Results of three T-tests revealed that APBs in general and in L3 production vocabulary learning outperformed their PMs. The results also showed that no significant difference was seen between APBs and PMs in L3 recognition vocabulary learning.